2018
DOI: 10.1142/s2575900018300047
|View full text |Cite
|
Sign up to set email alerts
|

How to choose the suitable animal model of polycystic ovary syndrome?

Abstract: Polycystic ovary syndrome (PCOS) is a gynecological metabolic and endocrine disorder with uncertain etiology. To understand the etiology of PCOS or the evaluation of various therapeutic agents, different animal models have been introduced. Considering this fact that is difficult to develop an animal model that mimics all aspects of this syndrome, but, similarity of biological, anatomical, and/or biochemical features of animal model to the human PCOS phenotypes can increase its application. This review paper ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 157 publications
0
9
0
3
Order By: Relevance
“…The results obtained in the present study using a model of adult Wistar rats induced to PCOS with a single dose of EV showed ovarian and estrous cycle changes, bone property modifications in vivo and in vitro, and alterations of ALP, OCN, and T in the plasma. Other studies have employed PCOS animal models 24,29,39 , with differences among the findings for PCOS rats being due to factors such as hormone type and dosage, route of administration, timing and duration of exposure, phase of the estrous cycle, and animal ages at the time of the study 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained in the present study using a model of adult Wistar rats induced to PCOS with a single dose of EV showed ovarian and estrous cycle changes, bone property modifications in vivo and in vitro, and alterations of ALP, OCN, and T in the plasma. Other studies have employed PCOS animal models 24,29,39 , with differences among the findings for PCOS rats being due to factors such as hormone type and dosage, route of administration, timing and duration of exposure, phase of the estrous cycle, and animal ages at the time of the study 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the etiology of PCOS and evaluation of the longterm risks of PCOS, in relation to bone development and metabolic and reproductive diseases, requires the development of suitable animal models 24 . Information is limited concerning methods for establishing animal models of PCOS, although several animal models have been developed and studied for the human PCOS [24][25][26][27][28][29] . However, the etiology of PCOS is still unclear, due to its complex manifestation as a syndrome and the limitations of translational studies using animals.…”
mentioning
confidence: 99%
“…The scoring system was obtained from the previous study by Tamadon et al ( 2018 ). All the major diabetic outcomes in the proposed models are included and compared to human diabetic state, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We used a comparison table in order to magnify the similarities and differences between the mentioned methods ( Tables 1 , 2 ). Also, scoring was suggested in order to choose the best model of hyperglycemia with the highest possible similarities to human among available ones ( Tables 3 , 4 ) based on the previous scoring principles for animal modeling of polycystic ovary syndrome as a metabolic disease (Tamadon et al, 2018 ). A verity of criteria is considered as laboratory workmanship and biological resemblance to human T2DM state.…”
Section: Introductionmentioning
confidence: 99%
“…According to the NIH, Rotterdam, and AE-PCOS conferences, hyperandrogenism is the most important diagnostic criteria of PCOS (3). Among androgenic animal models of PCOS, prenatal androgenized PCOS models displayed a set of reproductive and metabolic features of human PCOS (4).…”
Section: Introductionmentioning
confidence: 99%